A mild and scalable one-pot synthesis of N-substituted 2-aminobenzimidazoles via visible light mediated cyclodesulfurization - Tanawat Rerkrachaneekorn; Rose Malina Annuur; Soraya Pornsuwan; Mongkol Sukwattanasinitt; Sumrit Wacharasindhu (Scientific Reports)
Abstract A visible light mediated photocatalyst-free synthesis of N-substituted 2-aminobenzimidazoles directly from o-phenylenediamines and isothiocyanates is developed in a one-pot fashion. This one-pot reaction proceeds through three steps: N-substitution of o-phenylenediamines, thiourea formation and visible light mediated cyclodesulfurization. This method enables the rapid and efficient synthesis of structurally diverse N-substituted 2-aminobenzimidazoles, achieving yields up to 92% across 69 examples. The practicality of the reaction is demonstrated by gram-scale synthesis. The key advantages of this method include the use of less toxic solvent in aqueous media, the elimination of photocatalyst, and a simple, practical setup (one-pot, open-flask, and ambient temperature). Mechanistic insights are gathered through control experiments, including light on/off cycles and radical inhibition studies. The results indicate that the reaction involves with radical pathway mediated by visible light.